Determination of Testosterone level as predictor for insulin resistance in young men with family history of type2 diabetes and hypertension. (Baghdad Science Journal, 2025)
Background: Insulin resistance is associated with metabolic syndrome , type 2 diabetes and representing a risk factor for cardiovascular disease . This relationship may be modulated to some extent by age related changes in sex hormone status.. In particular, reduced total testosterone (TT) levels have been associated with insulin resistance and subsequent risk for developing type 2 diabetes. Aim of study: we examined whether low total testosterone level were associated with insulin resistance in young adult men. Methods: a total of 83 men (young adult men) divided into 2 group : (group1 ) 49 men with a risk factor for insulin resistance(with a family history of type2 diabetes and hypertension) and (group2) 34 men without any risk factor aged (20-40) years. Age, body mass index (BMI) and waist circumference were measured. Early morning, they were assayed for total testosterone, and insulin levels. Insulin resistance was assessed using a homeostatic model (HOMA-IR). Results: Total testosterone, declined progressively across increasing quintiles of HOMA-IR as a mean of(4.49±1.87) ng/ml in group1 compared mean (7.82±2.21) ng/ml in group 2 and correlated inversely with HOMA-IR( r = -0.424 , p = 002) also with insulin (r= -0.541) (p< 0.0001) in group1 . Total testosterone correlated inversely with BMI (r=-0.471 , p=0.001) in group1. There is a significant positive correlation between HOMA- IR of group1 and BMI (r= 0.472) (p